Existence and Location Results for Fully Nonlinear Boundary Value Problem of nth-Order Nonlinear System. (11th February 2009) - Sun, Li; Zhou, Mingru; Wang, Guangwa
Abstract : By appropriate bounding function pair and modified functions, using the theory of differential inequalities, this paper presents the existence and location criteria of solutions for the system of general n th-order differential equations with nonlinear boundary conditions. We give an example showing that the results are sharp. Our results extend many existing results.